Prevalence and Triggering Factors Associated with Mobile Phone Addiction among University Students in Bangladesh: - Ghosh, Antora; Sara, Sabiha Shirin; Nath, Chuton Deb; Talukder, Ashis (International Journal of Medical Science and Clinical Research Studies, 2022)
Background Nowadays, mobile phones are constantly being improved by enlarging upon their functionalities, which in turn increases the tendency of overuse and addiction. This study aimed to find the prevalence and factors associated with mobile phone addiction (MPA) among university students in Bangladesh. Methods This study recruited 379 participants by a self-administrated online based e-questionnaire using a cross section design. Leung’s Mobile phone Addiction Index Scale was used to assess MPA. In addition, logistic regression analysis was used to explore the associated factors for MPA. Results The overall prevalence of MPA was 42.2 % among the current university students. However, the addiction rate was 45.7 % among <25 years old participants. Spending time on the social media sites and lose sleep due to late night internet device activity were the reasons for MPA among university students in Bangladesh. Participants age less than 25 years and studying in undergraduate level had a higher chance of MPA. Conclusion This study exposed that the prevalence of MPA was comparatively higher among younger participants. Spend time on social media sites and lose sleep due to late night internet activity are the most significant determinants of MPA. Thus, raising awareness among the younger generation is most important to reduce MPA. The findings of the study can be used to support health and educational organizations design programs that will help prevent MPA among university students in Bangladesh.